Cognitive, social, and behavioral effects of music and motor intervention in children with autism spectrum disorder: the role of time of day - Kanzari, Chayma; Hawani, Aymen; Mkaouer, Bassem; Mrayeh, Maher; Marsigliante, Santo; Muscella, Antonella (Frontiers in Pediatrics, 2025)
This study aimed to determine the effect of 12 weeks of specific training (combining movement and music intervention) on children with autism spectrum disorders (ASD), specifically by comparing the time of day (morning vs. afternoon) with cognitive functions, mood, and social integration. Thirty children (19 males, 11 females; mean age 7.8 ± 1.27 years) were randomly assigned to two groups: an Intervention Group and a Control Group (CG). The intervention protocol consisted of combined sessions of training, music, and motor activities, administered in a counterbalanced order: one session in the morning (9:00–9:45 a.m.) and one in the afternoon (4:00–4:45 p.m.). The control group continued their regular physical activity. Children were assessed at baseline and post-intervention for cognitive functions (Trail Making Test), maladaptive behaviors (RCS), and enjoyment (PACES). A repeated-measures ANOVA was used to analyze the interaction between the music and movement intervention and time of day. Results showed a significant increase in enjoyment in both experimental groups (morning and afternoon) compared to the control group (p < 0.001), with no significant difference between the morning and afternoon groups (p = 0.743). After 12 weeks, the experimental groups showed significant improvements in both stereotypical behaviors (p < 0.001) and cognitive functions (p < 0.001). However, the time of day did not significantly influence these improvements (p = 0.133 for stereotypical behaviors and p = 0.681 for cognitive functions). Significant improvements were observed in affective/emotional (p < 0.001) and motor control behaviors (p < 0.001), which partially reflect reductions in maladaptive behaviors. However, specific measures of social engagement did not show statistically significant changes (p > 0.05). Our study found no effect of time of day on the outcomes for children with autism spectrum disorders.